Narratives of Social Mobility in the Post-Industrial Working Class and the Use of Credit in Chilean Households - Alejandro Marambio-Tapia (Revue de la Régulation)
This paper examines how the frequent and extended use of credit as a social asset in lower-income families and how the interpretation of financialisation practices has led to a particular discourse on social mobility. Specifically, it addresses the process of credit expansion by department stores and how it relates to lower-income families, i.e. the post-industrial working class, who tend to both offer and consume credit products; the lower-middle class; and low-skilled entrepreneurs. Credit has transcended the boundaries of economics. It has become a valuable asset for achieving the goal of providing a « decent life » and is at the core of the lower-income groups’ purchasing and budgeting practices. I will argue that this empirical method shows how the financialisation of household economies is more than a unidirectional process and that household arrangements, particularly moral ones, influence the use of credit and everyday economic behaviour. Lower-income groups are constructing a narrative of social mobility. This narrative convinces them that they are part of a « new middle class », defined fundamentally as people who mobilise credit as an asset for achieving social goals instead of relying on State welfare or constructing identity through educational achievement or occupational mobility.